2014
DOI: 10.1038/jhg.2014.77
|View full text |Cite
|
Sign up to set email alerts
|

GST Theta null genotype is associated with an increased risk for ulcerative colitis: a case–control study and meta-analysis of GST Mu and GST Theta polymorphisms in inflammatory bowel disease

Abstract: Glutathione S-transferases (GSTs) are important in the detoxification of many compounds, including reactive oxygen species. Polymorphisms in GSTs resulting in a decreased enzyme activity might enhance the risk for inflammatory bowel disease by eliciting a state of oxidative stress. Previous case-control studies showed divergent results and were frequently limited in sample size; therefore we conducted a meta-analysis including results from our case-control study. For the case-control study, we genotyped 552 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…6 Of the members of GSTs, glutathione S-transferase theta 1 (GSTT1), and GSTM1 in particular have become a recent target of active investigation into their role in increased susceptibility to IBD, Behçet's disease (BD), or other autoimmune diseases such as primary sclerosing cholangitis when either of the two GSTTs lose their function. 2,7,8 Deletion of the GSTT1 gene, a 50 kb genomic sequence containing the entire gene located on chromosome 22q11.2, results in a GSTT1-null genotype, 5,9 fails protein synthesis, and can decrease the ability to detoxify damaging compounds. 10 The GSTT1 null genotype leads to the absence of a functional GSTT1 enzyme 9,11 and results in increased susceptibility to a number of diseases, including IBD.…”
Section: Introductionmentioning
confidence: 99%
“…6 Of the members of GSTs, glutathione S-transferase theta 1 (GSTT1), and GSTM1 in particular have become a recent target of active investigation into their role in increased susceptibility to IBD, Behçet's disease (BD), or other autoimmune diseases such as primary sclerosing cholangitis when either of the two GSTTs lose their function. 2,7,8 Deletion of the GSTT1 gene, a 50 kb genomic sequence containing the entire gene located on chromosome 22q11.2, results in a GSTT1-null genotype, 5,9 fails protein synthesis, and can decrease the ability to detoxify damaging compounds. 10 The GSTT1 null genotype leads to the absence of a functional GSTT1 enzyme 9,11 and results in increased susceptibility to a number of diseases, including IBD.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding GSTT1 / M1 genes, both homozygous GSTT1 and GSTM1 deletion polymorphisms were shown to be associated with UC in Central China ( Ye et al, 2011 ), northern India ( Mittal et al, 2007 ), and in Turkish population ( Buyukgoze et al, 2013 ). Conversely, studies in Denmark ( Ernst et al, 2010 ) and Holland ( Broekman et al, 2014 ) as well as in Israeli Jews ( Karban et al, 2011 ) failed to demonstrate any relationship between GSTT1 / M1 loci and the risk of UC. Likewise, the GSTP1 rs1695 polymorphism showed significant association with UC in Central China ( Ye et al, 2011 ) and no association in Denmark ( Ernst et al, 2010 ).…”
Section: Discussionmentioning
confidence: 97%
“…As a result, 16 individual studies from 11 publications were included in the analysis. These studies involved a total of 3366 cases and 6013 controls [17-24, 32-34]. The main characteristics of the 16 included studies in our meta-analysis are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…There were 146 studies excluded after reviewing the abstracts and full texts. Thus, 11 publications were included in the meta-analysis [17-24, 32-34]. There were five publications that assessed the association of the GSTT1 null genotype with CD and five publications for UC.…”
Section: Resultsmentioning
confidence: 99%